2012
DOI: 10.1089/fpd.2011.1111
|View full text |Cite
|
Sign up to set email alerts
|

Sanitation of Selected Ready-to-Eat Intermediate-Moisture Foods of Animal Origin by E-Beam Irradiation

Abstract: To optimize the sanitation treatment of ready-to-eat (RTE) intermediate-moisture foods (IMF), the behavior of Listeria monocytogenes Scott A (CIP 103575), L. innocua (NTC 11288), Salmonella enterica serovar Typhimurium (CECT 443), and Escherichia coli O157:H7 (CECT 4972) following treatment with electron-beam irradiation has been studied. As food matrixes, three RTE vacuum-packed products (Iberian dry-cured ham, dry beef [cecina], and smoked tuna) were used. Although an irradiation treatment is not necessary w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…typhimurium [81]. Publications [37, 61, 82] have repeatedly confirmed that the resistance of S. typhimurium to irradiation is significantly higher than that of S . enteritidis , and the D -value for the former organism is in the level of 0.45–0.50 kGy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…typhimurium [81]. Publications [37, 61, 82] have repeatedly confirmed that the resistance of S. typhimurium to irradiation is significantly higher than that of S . enteritidis , and the D -value for the former organism is in the level of 0.45–0.50 kGy.…”
Section: Resultsmentioning
confidence: 99%
“…However, reports show that E-beam treatments at doses lower than 3 kGy did not affect the textural features of several meat products, including turkey beast rolls [86], cooked ham [34], dry ham [87], and fermented sausages [35]. These opposed differences may occur because pork loin is a raw meat, whereas the former items are transformed meat products with a higher dry matter content and, therefore, they present a more robust texture that may be less sensitive to physical technologies, such as irradiation and light pulse [37, 88]. During storage, the only clear difference observed affected adhesiveness, which increased with a longer storage time ( P < 0.05), which is probably related with the formation of slime by the Gram-negative bacteria [69, 74].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrolysis tubes were attached to a system, which allows the connection of nitrogen and vacuum lines without disturbing the sample. The tubes were placed in an oven at 110°C for 24h (Cambero et al, 2012). The tubes were then opened and the contents of each tube were filtered and evaporated until dryness in a rotary evaporator.…”
Section: Amino Acids Determinationmentioning
confidence: 99%
“…Electron beam (E‐beam) treatment is considered a process that can ensure that food safety standards are met without significant losses in food quality (Li & Farid, ; Pillai & Shayanfar, ; Roberts, ). Moreover, several authors have described its efficacy in reducing L. monocytogenes in various meat products, such as bologna, frankfurters, cooked pork and turkey ham (Foong, Gonzalez, & Dickson, ; Kudra et al, ), pork and beef loin (García‐Márquez, Cambero, Ordonez, & Cabeza, ; Yim, Jo, Kim, Seo, & Nam, ), duck meat (An et al, ; An, Jo, Akram, Suh, & Kwon, ), fermented sausages (Cabeza et al, ), and dry‐cured and cooked ham slices (Benedito et al, ; Cabeza et al, ; Cabeza et al, ; Cambero et al, ; Hoz, Cambero, Cabeza, Herrero, & Ordonez, ).…”
Section: Introductionmentioning
confidence: 99%